Rehabilitation and Reintegration of Women and Children Returning from Violent Extremist Contexts: A Rapid Review to Inform Program and Policy Development - Bunn, Mary (Terrorism and political violence, 2024)
This rapid review used a systematic approach to examine the available literature on rehabilitation and reintegration (R&R) programs for women and children returning from contexts of violent extremism, examining common assumptions, inputs, activities and outcomes across diverse settings. Fifty-one documents including peer reviewed articles and grey literature were included in the analysis. The most common program activities identified included mental health services, community level social programs, promoting school and vocational enrollment, regular health services, and parenting training & education, though there was a lack of consensus around core program components. The analysis points to the need for a robust set of inputs and resources to implement R&R programs including government officials, child welfare, mental health professionals, teachers, law enforcement, healthcare, community leaders, and extended family. The review also uncovered a number of gaps. This includes the need to create clear and analytically distinct definitions of rehabilitation and reintegration that are applicable and relevant to key stakeholders, delineating age-appropriate activities and outcomes for young children, youth, and adults, defining frameworks for service delivery and coordination of stakeholders, and placing R&R programs within existing domains of public safety and restorative justice.